Strain investigation of infill frames using FEA package MSC NASTRAN. (April 2021) - Yadav, Golla Swamy; Anuradha, P.
Highlights: MSC NASTRAN. Infill frame with different openings. Infill frame with door opening and strains. Abstract: Masonry infill is usually neglected in the design and it is treated as a non-structural element instead of its stiffness and lateral resistance capacity. Their presence in the RC frame could also affect the lateral load resistance. The interaction of infill presence in the RC frame will also depend on the aspect ratio of frame and openings presence in the infill. The infill collapse initiated disaster of RC Framed structures are mainly concerned by the researchers recently. Many researchers considered experimentation up to a single-story single bay frame may be due to constraints in their facilities. A 3-bay 3-Storey Frame is considered in the present study using finite element package using MSC NASTRAN for different frame such as bare frame, Infill frame with different openings provided in it, and meshing was done finally strains were taken at middle third distances on each member of the internal panel of the bare frame, Infill frame, Infill frame with window opening, Infill frame with door opening, Infill frame with window and door openings and a comparison was made with infill frame and presence of openings in the infilled frame.